Managing educational policy implementation at secondary education level - Martha-Rose Ifeoma Uwaezuoke (Edukasiana: Jurnal Inovasi Pendidikan, 2023)
The paper which examined managing education policy implementation at the secondary education level for effective practice was guided by two research questions and two hypotheses. The study adopted descriptive survey research design. The population of the study consists of twenty-one (21) public secondary schools in Aguata Local Government Area of Anambra State. The study utilized simple random sampling technique to select eleven (11) public secondary schools, from the selected schools, eleven (11) principals and thirty-five (35) teachers were picked for the study making a total of three hundred and ninety-six (396). Self-designed instrument entitled “Managing Education Policy Implementation for Effective Practice Questionnaire” (MEPIEPQ) was used to elicit information from the respondents. Validity of the instrument was ensured using expert reviews while Cronbach Alpha was used to compute its reliability which yielded an index of 0.82. Frequency counts and mean ratings were used to answer the research questions while t-test statistics was used to test the hypotheses at 0.05 level of significance. The findings revealed among others that managing education policy implementation at the secondary education level is challenged first by educational resources deficiency and concludes that one of the determinants of educational policy implementation is the provision of quality educational resources in sufficient quantity which is totally lacking in managing education policy implementation in Aguata, LGA of Anambra State. The researcher therefore recommended that the policy blue-print should be backed up with the sufficient educational resources for its implementation to enhance effective practice and functional educational delivery process.